2013
DOI: 10.1177/1094670512474841
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Endogenous Motivations on Adoption of IT-Enabled Services

Abstract: Transformative services represent a crucial topic in future service research. Particularly in the energy sector, consumer adoption of transformative-often IT-enabled-services is essential to increased environmental sustainability. As adopting these services increases both individual and collective well-being, research has to delve more deeply into the origins of consumers' motivations. For this reason, this study aims at augmenting the understanding of how different types of motivation determine consumers' int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 86 publications
(163 reference statements)
1
41
2
Order By: Relevance
“…Few studies have employed a design-oriented approach to develop IS artifacts that actually have an impact on environmental sustainability. A particularly striking result of our review is the monothematic focus on energy consumption of most smart energy research published in IS journals, while in other outlets we find a number of studies on ICT's role in smart energy, addressing issues related to energy generation, transmission, storage, and consumption (e.g., Kranz and Picot 2011b;Catulli and Fryer 2012;Römer, Reichhart, Kranz, and Picot 2012;Gorsevski et al 2013;Wunderlich et al 2013;Schmidt, Eisel, and Kolbe 2014).…”
Section: Where Do We Stand?mentioning
confidence: 97%
See 2 more Smart Citations
“…Few studies have employed a design-oriented approach to develop IS artifacts that actually have an impact on environmental sustainability. A particularly striking result of our review is the monothematic focus on energy consumption of most smart energy research published in IS journals, while in other outlets we find a number of studies on ICT's role in smart energy, addressing issues related to energy generation, transmission, storage, and consumption (e.g., Kranz and Picot 2011b;Catulli and Fryer 2012;Römer, Reichhart, Kranz, and Picot 2012;Gorsevski et al 2013;Wunderlich et al 2013;Schmidt, Eisel, and Kolbe 2014).…”
Section: Where Do We Stand?mentioning
confidence: 97%
“…(1) First order effect: Direct impacts on the environment due to the physical existence and use of IT, often labeled as "Green IT" (e.g., Dao et al 2011;Molla 2009;Murugesan 2008;Karanasios, Cooper, Deng, Molla, and Pittayachawan 2010;Schmidt, Erek, Kolbe, and Zarnekow 2011;Opitz, Thies, Erek, Kolbe, and Zarnekow 2013;Reiter, Fettke, and Loos 2013;Ryoo and Koo 2013;) (2) Second order effect: Enabling effects of ICTs in other sectors such as energy, logistics, mobility, and manufacturing that lead to more sustainable business operations, often labeled as "Green (by) IS" (Watson et al 2010a;Watson, Boudreau, Li, and Levis 2010b;Butler 2011;Kranz and Picot 2011a;Sarkis, Zhu, and Lai 2011;Loeser, Erek, and Zarnekow 2012;Brandt, Feuerriegel, and Neumann 2013;Busse et al 2013;Hilpert et al 2013;Stiel and Teuteberg 2013;Wunderlich et al 2013;Koo, Chung, and Ryoo 2014) (3) Third order effect: Systemic effects of ICTs causing medium-or long-term changes of behavior and economic structures towards more eco-sustainable practices, often labeled as "Green IS" (Watson et al 2011;e.g., Loock et al 2013;Seidel et al 2013) To analyze where the field is going, we have conducted a literature review of articles in major IS journals. Our search included the AIS basket of eight leading IS journals (European Journal of Information Systems, Information Systems Journal, Information Systems Research, Journal of AIS, Journal of Information Technology, Journal of MIS, Journal of Strategic Information Systems, and MIS Quarterly), Electronic Markets, and Business & Information Systems Engineering.…”
Section: Where Do We Stand?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the model could be tested in various contexts, we will focus on Green IS with We predict that all constructs related to the PSD model are likely to influence all types of PLOCs, because the persuasive support categories are likely to trigger different types of motivations and either cause alignment or misalignment with the personal norms. Additionally, prior research [39,62,63] showed that all types of PLOCs have influence on the individuals' attitudes, and therefore, we assume that these relationships will hold up in the current study as well. Moreover, as suggested by the theory of reasoned action (TRA) [20] and the theory of planned behavior (TPB) [1], we expect to see strong connections between attitude towards Green IS and intention to adopt them.…”
Section: Research Model and Hypothesesmentioning
confidence: 78%
“…[1], [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13] H1 Basic ICT Skill has a positive effect on perceived usefulness.…”
Section: G Basic Ict Skill (Bicts)mentioning
confidence: 99%